Arizona Quail: Species in Jeopardy? - Ron Engel-Wilson; William P. Kuvlesky Jr. (National Quail Symposium Proceedings, 2017)
We begin the 21st century with the Midwestern northern bobwhite (Colinus virginianus) range reduced to a small portion of its historic distribution. This precipitous decline occurred largely during the last quarter of the 20th century, coincident with widespread intensive agricultural land use, unchecked natural plant succession, and frequent severe weather. Various bobwhite enthusiasts of the 1960s–1980s era including Klimstra, Dumke and Stanford had evaluated agricultural land use trends and predicted the near demise of bobwhites that we now lament. Alarmed upland bird hunters have repeatedly spurred policy makers and administrators into action. However, because bobwhites still are only an incidental product of modern agriculture, the potential for reversing declining population trends is limited. Moreover, as society and the wildlife profession become progressively less interested in consumptive uses of wildlife, the political will to appropriate agency resources for bobwhites per se is disappearing. Such a pattern has been seen in the Midwest where bobwhite conservation has become a marginal issue on the periphery of the species’ range (e.g., Ia., Wis., Mich., Ont.). This paradigm shift is occurring in much of the bobwhite’s historic range where habitat and bird populations remain at low levels. The result is that bobwhite culture as we know it (i.e., research, management, and hunting) will decline and be replaced by ecosystem conservation. At the state and national level (e.g., North American Bird Conservation Initiative, Conservation and Reinvestment Act), potential funding for restoration and management of savannas, prairies, agroecosystems, etc., can provide habitat for bobwhites. Bobwhite enthusiasts should embrace this change, and participate in the process to ensure that the needs of bobwhites are included. Importantly, our knowledge base for bobwhites is relatively strong and should bolster efforts to include needs of bobwhite in ecosystem management.
Keywords: abundance; access; agriculture; artificial propagation; attitude; biodiversity; Colinus virginianus; history; hunting; Midwest; Phasianus colchicus; ring-necked pheasant; socioeconomic; urban; wildlife profession